Crystallization behavior and compatibility analysis of palm kernel stearin/anhydrous milk fat blends and application - Su, Yi; Chai, Xiu-hang; Tan, Chin-Ping; Liu, Yuan-fa (Wiley, 2024)
Abstract: In this paper, the compatibility, phase behavior, and crystallization properties of the binary blends of palm kernel stearin (PKS) and anhydrous milk fat (AMF) were investigated by analyzing the solid fat content (SFC), thermal properties, polymorphism, and microstructure, with the aim of providing theoretical guidance for the blending of oils. The results showed that the PKS content primarily determined the SFC trend of the binary blends. However, the binary blends demonstrated poor miscibility and eutectic behavior was predominantly observed in the system, particularly at higher temperatures. Only α and β′ forms appeared in this blended system. Simultaneously, the addition of PKS elevated the liquid phase transition temperature of the binary blends, considerably significantly increased their crystallization rate when the addition of PKS was more than 20% and increased the density and size of the fat crystals. Finally, the mixing design optimization method was used to get the most suitable ratio of the binary blends in the refrigerated cream system with PKS:AMF to be 0.914:0.086. The cream prepared with the above binary blends was indeed superior in overrun and firmness and had high stability. Practical Application: Some fats with special advantages are often limited in their wide application because of their poor crystallization ability. In this paper, the crystallization ability of fats is improved, and their application scenarios are increased through the combination of fats, so as to provide reference for the production of special fats for food.